A Study of Best Practices in The Professional Performance of Islamic Religious Education Teachers at SMPN 1 Bermani Ilir - Alqomar, Shidik Wahidun; Auliya, Siti Khairiyatul; Susilawati, Susilawati; Angel, Tiara; Julia, Arini (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2025)
This study examines the best practices of the Islamic Religious Education (PAI) teacher at SMPN 1 Bermani Ilir, focusing on pedagogical effectiveness, character internalization, and professional competence in classroom management. Using a qualitative descriptive approach, data were gathered through classroom observations, semi-structured interviews, and analysis of instructional documents. The findings reveal that the teacher employs a combination of contextual teaching, interactive learning, moral modeling, value habituation, and reflective dialogue to enhance students’ understanding and internalization of Islamic teachings. Additionally, the teacher demonstrates strong professional competence through structured lesson planning, ethical conduct, emotional intelligence, and adaptive instructional strategies. These best practices contribute significantly to creating a holistic learning environment that supports students’ cognitive, moral, and spiritual development. The study highlights the importance of integrating pedagogical skills, ethical professionalism, and character-based approaches in strengthening the overall quality of PAI instruction.